2016
DOI: 10.1016/bs.irn.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of BK Channels by Ethanol

Abstract: In alcohol-naïve systems, ethanol (<100 mM) exposure of calcium-gated BK channels perturbs physiology and behavior. Brief (several minutes) ethanol exposure usually leads to increased BK current, which results from ethanol interaction with a pocket mapped to the BK channel-forming slo1 protein cytosolic tail domain. The importance of this region in alcohol-induced intoxication has been addressed in Caenorhabditis elegans slo1 mutants. However, ethanol-induced BK activation is not universal as refractoriness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…BK channels are direct molecular targets of ethanol (Dopico et al, 2016), underlie a molecular mechanism of cellular tolerance to alcohol (Bettinger and Davies, 2014), and play a key role in alcohol withdrawal related phenotypes (Ghezzi et al, 2014; N'Gouemo and Morad, 2014; Kreifeldt et al, 2013; Kreifeldt et al, 2015). Along with evidence from Edenberg et al, 2010 who reported a similar association between SNPs within KCNMA1 and alcohol dependence in both European and African American samples, KCNMA1 represents a compelling candidate gene requiring further analysis.…”
Section: Genome-wide Association Studies Of Alcohol Dependencementioning
confidence: 99%
“…BK channels are direct molecular targets of ethanol (Dopico et al, 2016), underlie a molecular mechanism of cellular tolerance to alcohol (Bettinger and Davies, 2014), and play a key role in alcohol withdrawal related phenotypes (Ghezzi et al, 2014; N'Gouemo and Morad, 2014; Kreifeldt et al, 2013; Kreifeldt et al, 2015). Along with evidence from Edenberg et al, 2010 who reported a similar association between SNPs within KCNMA1 and alcohol dependence in both European and African American samples, KCNMA1 represents a compelling candidate gene requiring further analysis.…”
Section: Genome-wide Association Studies Of Alcohol Dependencementioning
confidence: 99%
“…Murray [63] showed that administration of a posterior pituitary extract inhibited alcohol-induced diuresis, and it is widely accepted that alcohol exerts its diuretic action by inhibiting vasopressin release. Elegant work by the groups of Lemos and Treistman [64] showed that this effect occurs in vitro in preparations of isolated nerve terminals at alcohol levels as low as 10mM and Dopico and others have provided a cellular and molecular level explanation for this action of alcohol, in terms of its ability to enhance the opening of Ca 2+ -activated K + (BK) channels and thereby reduce the release of vasopressin [65] reviewed in [66]. Although the diuresis elicited by alcohol may be considered to be a peripheral effect of the drug, the mechanism of BK channel modulation by which this occurs is a common one, and one by which alcohol may influence neurons within the CNS, in addition to those in the HPA.…”
Section: Hypothalamic-pituitary Axismentioning
confidence: 99%
“…For positive selection, the phagemid library was panned against HEK293 cells expressing the ZERO isoform of the human BKa channel (hSLO). The ZERO isoform was chosen because it is widely expressed in the mammalian nervous system and is sensitive to ethanol (Pietrzykowski et al, 2008;Dopico et al, 2016). For negative selection, the library was screened against another ethanol target protein, the glycine receptor (hGlyRa1) as well as another calcium-sensitive potassium channel (rSK2) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The channel's probability of opening P o , probability of opening, changes within minutes after ethanol exposure. However, whether the P o goes up or down, either transiently or more persistently, depends upon regulatory subunit expression, post-translational modifications, and the channel's microenvironment (Dopico et al, 2016).…”
Section: Introductionmentioning
confidence: 99%